The effect of adding casein hydrolysate as a protein source in the culture of the bacteria Paenibacillus polymyxa at wilker office of food and horticultural plants protection (PTPH) Bojonegoro - Nanda Putri Insan Khasana; Miwing Nurul W; Annisa Khumaira (International Journal of Health Science and Technology, 2021)
Agencia (Biological Control Agents) are currently widely used to control pests and diseases or plant-disturbing organisms. One of the biological agents that has many benefits for controlling several types of diseases in both food crops and horticulture is Paenibacillus polymyxa. These bacteria are beneficial in nitrogen fixation, promotion of plant growth, solubilization of soil phosphorus, and production of exopolysaccharides, hydrolytic enzymes, antibiotics, and cytokinins. Paenibacillus polymyxa also produces polymyxin antibiotics and it is known that these bacteria contain the hormone gibberellins. Casein hydrolyzate is one of the growth media that can be used for the growth of microorganisms. The media is a complex mixture of 18 amino acids, vitamins, calcium, phosphate, and several microelements which results in their high price. Casein hydrolyzate is known to be more effective for plant tissue culture. Therefore, the purpose of this study was to determine whether the amino acid content in casein hydrolyzate could affect the growth of bacteria Paenibacillus polymyxa. The simple medium used in this study was soybean boiled water. Soybean as an alternative medium for protein sources to substitute beef extract, beef extract, and bacto peptone for the growth of bacteria Paenibacillus polymyxa. Based on TPC (Total Plate Count) calculations with graded dilution in Paenibacillus polymyxa, it was found that there was no difference in the number of bacteria to the addition of casein. This shows that bacteria can grow optimally even though casein hydrolyzate is not given during the growth process.